Perancangan Telescopstick Menggunakan Quality Function Deployment (QFD) - Deri Teguh Santoso; Jojo Sumarjo; Ratna Dewi Anjani (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
As the development of science is always accompanied by high-technology applications, innovation is needed to support the implementation of a technology. Almost all human activities are currently assisted by tools. Most of the families in Indonesia has a TV antenna. However, There are difficulties in the installation of antenna stick. Therefore, designing a tool in the form of a stick that can be elongated/shortened automatically is necessary for ease of use. The tool is called "Telescopstick". In addition, to be a tool for TV antenna pole, it is designed for multifunctional purpose because there is a joint at the end of this tool that can be connected with other tools, so it can serve as a substitution of a lamp, duster and etc. This tool is designed to be robust and lightweight, made of polyethylene pipe in a consideration of the functions and needs of this tool. The mechanism of this tool is basically a pulley system that enables the change of its length dimension through the pull of wire. The wire pulling mechanism itself utilizes 12 Volt DC electric motor with energy provided by a battery. Quality Function Deployment (QFD) method is employed to design this tool because it focuses on a consumer-needs-based design process. The results show that the tool can replace conventional sticks which are easily destroyed and difficult to install and the availability of spare parts are easily obtained as well. The findings of this study can be used as effectively as possible for future research.Keywords: Telescopstick Design, Innovation, Polyethylene, Quality Function Deployment